Hubungan Antara Daya Tarik Antarpersonal Dengan Pengungkapan Diri Secara Online Pada Siswa Sekolah Menengah Atas Pengguna Media Sosial Di Surakarta - TRICYLIA DEWI, YOAN, Susatyo Yuwono, S.Psi, M.Si.,Psi (2016)
find the correlation between antarpersonal attraction and online self-disclosure, the effective contribution of antarpersonal attraction and online self-disclosure, the level of antarpersonal attraction and online self-disclosure. The subject of this research is 188 students from SMA Negeri 4 Surakarta and SMA Muhammadiyah 1 Surakarta who use social media. The data collection technique of this research is quota non random sampling. The approximation method of this research is Quantitative using measuring scale of antarpersonal attraction and scale of online self-disclosure. The data analysis technique of this research is the correlation analysis from Pearson using SPSS 15 for Windows program. By the outcome of data analysis, we can obtain the correlation coefficient 0,281 with sig. = 0,000; (p < 0,001) which means there is a significant positive relation between antarpersonal attraction and online self-disclosure of the high school student who use social media in Surakarta. The effective contribution of antarpersonal attraction's role for online self-disclosure is as big as 7,9 % and another factors influence the rest of it as big as 92,1 %. The variable of antarpersonal attraction has a mean empiric (RE) as big as 121,69 that one can say high category in middle level. Whereas the variable of online self-disclosure is known to have a mean empiric (RE) as big as 115,19 that one can say medium category in lower level. Keyword: Antarpersonal Attraction, Online Self-Disclosure, High School Student